INDUKSI TUNAS, MULTIPLIKASI DAN PERAKARAN Gyrinops versteegii (Gilg.) Domke SECARA IN VITRO - Aziz Akbar M; Eny Faridah; Sapto Indrioko; Toni Herawan (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2017)
Gyrinops versteegii (Gilg.) Domke is including one of superior agarwood-producing plants and naturally growing in Eastern Indonesia as Nusa Tenggara and Papua. Indonesia has been trading agarwood products both domestically and overseas which one of them is agarwood produced by G.versteegii. This study purpose was to develop an in vitro culture method for mass propagation of G. versteegii. Shoot induction conducted on MS medium supplemented with Benzyl Amino Purine (BAP) 0.7; 1.0; 1.5; and 2.0 mg/l. The shoots multiplication conducted on MS medium supplemented with the best concentration of BAP from shoot induction phase. The rooting of shoots conducted on half strength MS medium supplemented with interaction of Napthalene Acetic Acid (NAA) 0.01 mg/l with concentration of Indole-3-Butyric Acid (IBA) 1.0; 2.0; 3.0; and 4.0 mg/l. Epicotyl explant with a given concentration level of BAP 0.7 mg/l produce the highest rates number of shoots and shoot length compared to other explant respectively 4.8 shoots and 0.41 cm within 6 weeks. The best explant developments in the best medium able to promote the growth of the length and number of shoots are 0.28 shoots and 0.3 cm within 4 weeks. Explants easiest, quickest and most high sprouting ability as a factor of success in terms of multiplication is epicotyl. The combination treatment of material explant with concentration of BAP only affect to growth of shoots length. The combination treatment of NAA with concentration of IBA has no effect against root formation and growth rootlength.